Men's Coercive Condom Use Resistance: The Roles of Sexual Aggression History, Alcohol Intoxication, and Partner Condom Negotiation. (September 2018) - Davis, Kelly Cue; Gulati, Natasha K.; Neilson, Elizabeth C.; Stappenbeck, Cynthia A.
Condom use resistance (CUR) through coercive tactics is a significant public health concern. The present study investigated CUR risk factors through an alcohol administration experiment using a sexual risk analog with a community sample of male nonproblem drinkers ( N = 321). Utilizing a path analysis framework, results demonstrated that men with more severe sexual aggression histories displayed stronger in-the-moment power and control responses, which was associated with greater coercive CUR and unprotected sex intentions. A significant interaction between sexual aggression history, risk rationale, and alcohol condition also predicted coercive CUR intentions. These findings emphasize the relationship between sexual aggression and sexual risk behaviors and highlight the importance of targeting these constructs in intervention and prevention efforts.